"A Circular Council of People With Equal Ideas": The Mentoring Mosaic in a Preservice Teacher Education Program. Issue 2 (February 2017) - Davis, Susan A.
Mentoring in music education programs is such a ubiquitous part of the process; it is sometimes overlooked or subsumed under other categories. The purpose of this article is to highlight mentoring relationships within an undergraduate music teacher education program. Formal, informal, vertical, and horizontal mentoring are examined from the perspectives of undergraduate preservice music teachers working in a community-university partnership. The data are culled from a 14 month, intrinsic case study of the University of South Carolina String Project, designed to examine the participant experience for all member groups within the string project—the undergraduate preservice teachers, the community students, and the faculty. Mentoring relationships are explored as a critical component of experience for the preservice teachers. Their voices are presented here to illustrate the value they placed on mentoring, as well as the challenges that emerged in construction of a mentoring mosaic as part of their preservice teaching experience.